The Influence of Desensitization on The Recovery of Allergy, In articular Asthma - M. P. Damanik; A. Samik Wahab; Suminta Suminta; Ediyono Ediyono; Ismangoen Ismangoen (Paediatrica Indonesiana, 1984)
An evaluation was carried out to determine the effect of desensitization on 62 asthmatic patients under the age of 14 years. Preceeding the evaluation, an intracutaneous skin test was conducted of which all patients produced positive reactions to one or more allergen types. Desensitization was carried out for at least 5 months (up to the 30th injection), .with the following results : good, 45 (72,57%); decreased symptoms 12 ( 19.03%), and constant (no change), 5 (8,4%). All patients reached the maximum dosage ( 1 cc ), except 2 patients whom, given the maximum dosage, become worse, therefore suitable dosages were maintained (0.5 - 0. 7 cc). Therapy for one type of allergen was also proven as follows: house dust, good 1 (100%); mite, good 1 (100%); bacteria, good 14 (87.5%), fungi, good 1 (100%). Result of therapy for 2 types of allergen : f' , use dust +splinter of human dunder in 31 patients was : good 24 (77.4%); constant 7 (22.59%). Whilst therapy for 3 types of allergen : house dust + splinter of human dunder + mite revealed : good, 4 (33.4%); decreased symptoms, 3 (25%); and constant, 5 (41.6%). It may therefore be concluded that the greater the number of allergens, the less effective the desensitization becomes.